Detection of H-type bronchoesophageal fistula in a newborn: A case report and literature review. Issue 8 (25th February 2022) - Li, Huaying; Yan, Li; Ju, Rong; Li, Biao
Abstract: Rationale: Congenital tracheoesophageal fistula (TEF) is a rare developmental malformation. The H subtype accounts for approximately 4% of TEFs. Unlike other TEFs, the H-type is not accompanied by esophageal atresia and has nonspecific clinical symptoms, and its specific anatomical abnormalities are not always readily apparent. Furthermore, none of the currently available diagnostic methods for H-type TEF have absolute sensitivity, resulting in misdiagnoses, and accurate diagnoses are often delayed even until adulthood; in our case, we detected a congenital bronchoesophageal fistula, which is even more rare than regular H-type TEF, through a technique that was not previously reported for newborns, involving bronchoscopy, with methylene blue injected through an esophagoscope. We believe that we have provided this kind of case first in newborns. Furthermore, because there is not one literature summarizing the clinical symptoms and the effective methods up to now, we still are not clear which detective method is more efficient or accurate, especially in newborns, so it is very necessary to summarize and compare for improving the early diagnosis of TEFs; our study makes a significant contribution to the literature because we collated previously reported cases, including the clinical features and the usefulness and success rates of major tests, which will be very helpful for the early diagnosis of TEFs. Patient concerns: A newborn male presented with an array of nonspecific clinical symptoms from birth, leading to pneumonia and mechanical ventilation. Oral feeding led to an improvement in most but not all symptoms, which returned when oral feeding was resumed. A second round of confirmatory tests was still unable to detect the cause. Diagnosis: The diagnosis of H-type bronchoesophageal fistula was established through a technique that was not previously reported for newborns, involving bronchoscopy, with methylene blue injected through an esophagoscope. Interventions: The surgery was performed after diagnosis, and the bronchoesophageal fistula was successfully repaired. Outcomes: The patient was discharged on postoperative day 7, and his status was reported to be normal at a follow-up visit 8 months after surgery. Lessons: H-type TEF is a rare congenital abnormality, and its early diagnosis is highly difficult, especially bronchoesophageal fistula. Increased oral saliva and air-filled stomachs are characteristic manifestations. Bronchoscopy combined with esophagoscopy can improve the rate of early diagnosis. A combination of tests can improve the detection rate.